Reinforcement of cell-mediated immunity driven by tumor-associated Epstein-Barr virus (EBV)-specific T cells during targeted B-cell therapy with rituximab - Tischer-Zimmermann, Sabine; Bonifacius, Agnes; Santamorena, Maria Michela; Mausberg, Philip; Stoll, Sven; Döring, Marius; Kalinke, Ulrich; Blasczyk, Rainer; Maecker-Kolhoff, Britta; Eiz-Vesper, Britta (Frontiers in Immunology, 2023)
Introduction In immunocompromised patients, Epstein-Barr virus (EBV) infection or reactivation is associated with increased morbidity and mortality, including the development of B-cell lymphomas. The first-line treatment consists of reduction of immunosuppression and administration of rituximab (anti-CD20 antibody). Furthermore, the presence of EBV-specific T cells against latent EBV proteins is crucial for the control of EBV-associated diseases. Therefore, in addition to effective treatment strategies, appropriate monitoring of T cells of high-risk patients is of great importance for improving clinical outcome. In this study, we hypothesized that rituximab-mediated lysis of malignant EBV-infected B cells leads to the release and presentation of EBV-associated antigens and results in an augmentation of EBV-specific effector memory T-cell responses. Methods EBV-infected B lymphoblastoid cell lines (B-LCLs) were used as a model for EBV-associated lymphomas, which are capable of expressing latency stage II and III EBV proteins present in all known EBV-positive malignant cells. Rituximab was administered to obtain cell lysates containing EBV antigens (ACEBV). Efficiency of cross-presentation of EBV-antigen by B-LCLs compared to cross-presentation by professional antigen presenting cells (APCs) such as dendritic cells (DCs) and B cells was investigated by in vitro T-cell immunoassays. Deep T-cell profiling of the tumor-reactive EBV-specific T cells in terms of activation, exhaustion, target cell killing, and cytokine profile was performed, assessing the expression of T-cell differentiation and activation markers as well as regulatory and cytotoxic molecules by interferon-γ (IFN-γ) EliSpot assay, multicolor flow cytometry, and multiplex analyses. Results By inhibiting parts of the cross-presentation pathway, B-LCLs were shown to cross-present obtained exogenous ACEBV-derived antigens mainly through major histocompatibility complex (MHC) class I molecules. This mechanism is comparable to that for DCs and B cells and resulted in a strong EBV-specific CD8+ cytotoxic T-cell response. Stimulation with ACEBV-loaded APCs also led to the activation of CD4+ T helper cells, suggesting that longer peptide fragments are processed via the classical MHC class II pathway. In addition, B-LCLs were also found to be able to take up exogenous antigens from surrounding cells by endocytosis leading to induction of EBV-specific T-cell responses although to a much lesser extent than cross-presentation of ACEBV-derived antigens. Increased expression of activation markers CD25, CD71 and CD137 were detected on EBV-specific T cells stimulated with ACEBV-loaded APCs, which showed high proliferative and cytotoxic capacity as indicated by enhanced EBV-specific frequencies and increased secretion levels of cytotoxic effector molecules (e.g. IFN-γ, granzyme B, perforin, and granulysin). Expression of the regulatory proteins PD-1 and Tim-3 was induced but had no negative impact on effector T-cell functions. Conclusion In this study, we showed for the first time that rituximab-mediated lysis of EBV-infected tumor cells can efficiently boost EBV-specific endogenous effector memory T-cell responses through cross-presentation of EBV-derived antigens. This promotes the restoration of antiviral cellular immunity and presents an efficient mechanism to improve the treatment of CD20+ EBV-associated malignancies. This effect is also conceivable for other therapeutic antibodies or even for therapeutically applied unmodified or genetically modified T cells, which lead to the release of tumor antigens after specific cell lysis.